Impact of Car-Free Day For Street Traders in Pekalongan District - Subekti, Slamet; Hermawan, Hendri (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2024)
This research seeks to reveal and obtain objective information about the impact of Car Free Day implementation in Kajen, Pekalongan on street vendors. This research uses a qualitative approach with a case study design. The location of the research was Kajen Square, the location of Car Free Day. The data sources were 5 street vendors and 3 Car Free Day visitors. From the results of data analysis, data were obtained which included (1) Production of Economic Activities of Street Vendors, (2) Distribution of Economic Activities of Street Vendors, (3) Public Consumption of Car Free Day Implementation, (4) Price Level of Products Sold by Street Vendors during Car Free Day in Kajen.